2022
DOI: 10.1111/een.13142
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and host plant species affect the performance and immunocompetence of an outbreak defoliator in northwestern Patagonia

Abstract: Rising temperature has been associated with increased occurrence of herbivorous insect outbreaks, explained by several direct and indirect mechanisms. Whereas natural enemies are known key drivers of forest‐defoliating insect cycles, indirect effects of temperature on insect's ability to defend against pathogens and parasitoids (e.g., immunocompetence), as well as the interaction with other mechanisms (e.g., diet), remain less explored. The aim of this study is to evaluate the effect of temperature and diet on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Under this scenario, higher abundances, more generations per season and a high level of defoliation are expected in the future. In the same vein, Serra et al [22] showed that the biological mechanism behind the higher population size is an increment in resistance to the action of parasitoids, which allows a higher survival of immature stages. If the increase in temperatures is lower than the upper thermal limit for the development of O. amphimone, we can thus expect that the intensity (level of defoliation) and extent (area defoliated) will increase in the following decades.…”
Section: Discussionmentioning
confidence: 97%
“…Under this scenario, higher abundances, more generations per season and a high level of defoliation are expected in the future. In the same vein, Serra et al [22] showed that the biological mechanism behind the higher population size is an increment in resistance to the action of parasitoids, which allows a higher survival of immature stages. If the increase in temperatures is lower than the upper thermal limit for the development of O. amphimone, we can thus expect that the intensity (level of defoliation) and extent (area defoliated) will increase in the following decades.…”
Section: Discussionmentioning
confidence: 97%